2014
DOI: 10.1016/j.sjbs.2013.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cadmium on the growth and antioxidant enzymes in two varieties of Brassica juncea

Abstract: Increasing contamination and higher enrichment ratio of non-essential heavy metal cadmium (Cd) induce various toxic responses in plants when accumulated above the threshold level. These effects and growth responses are genotype and Cd level dependent. An experiment was conducted to analyze the effect of Cd toxicity in Brassica juncea [L] Czern and Coss by selecting its two varieties Varuna and RH-30. Cadmium (0, 25, 50 or 100 mg CdCl2 kg(-1) of soil) fed to soil decreased the values of growth characteristics, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

10
53
2
6

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(71 citation statements)
references
References 22 publications
10
53
2
6
Order By: Relevance
“…It has been established that stress results in upregulated proline synthesis with a concomitant reduction in catabolism (Iqbal et al 2015). Our observation of proline and sugar accumulation in cadmium-stressed plants supports similar previous findings (Irfan et al 2014;Hashem et al 2016). The actual mechanism of cadmium toxicity is not well understood, and improving cadmium tolerance in plants through conventional methods may be the best alternative.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…It has been established that stress results in upregulated proline synthesis with a concomitant reduction in catabolism (Iqbal et al 2015). Our observation of proline and sugar accumulation in cadmium-stressed plants supports similar previous findings (Irfan et al 2014;Hashem et al 2016). The actual mechanism of cadmium toxicity is not well understood, and improving cadmium tolerance in plants through conventional methods may be the best alternative.…”
Section: Discussionsupporting
confidence: 90%
“…Reduced height and biomass due to cadmium stress corroborates with the findings in Triticum aestivum (Ci et al 2009), Brassica juncea (Irfan et al 2014) and Helianthus annuus (Abd_Allah et al 2015). The reduced height, leaf area and biomass in S. indicum due to cadmium stress were reversed following calcium application.…”
Section: Discussionsupporting
confidence: 74%
“…Antioxidant enzymes are crucial cellular components that maintain cellular redox potential. Irfan et al (2014) found a dose dependent increase in the activities of antioxidant enzymes in Brassica juncea subjected to Cd stress. Likewise, Mohamed et al (2012) reported that oilseed plants with greater activities for antioxidant enzymes presented a better ROS detoxification potential.…”
Section: Discussionmentioning
confidence: 89%
“…Proline acts directly as an antioxidant to protect the cell from free radical damage and maintains a more reducing environment that is favorable for phytochelation synthesis and cadmium sequestration ( Alayat et al, 2014). Also, accumulation of proline apparently protects the metabolic machinery, stabilizes the bio-membranes and macromolecules to prevent water loss and supported nutrient uptake to support growth performance in cadmiumstressed plants (Irfan et al, 2014). Finally, proline acts as a molecular chaperone capable of defending protein integrity and improving the activities of different enzymes (Szabados and Savoure, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, metal accumulator crop species take up and accumulate Cd in their tissues at high level, which not only poses threat to plant endurance, but also induces several toxic responses and raises the danger of food contamination (Irfan et al, 2014). Cd is thought to be the most harmful heavy metal because of its high solubility in water (Ali et al, 2014).…”
mentioning
confidence: 99%